Ethics of work and discipline in transition : Uljanik in late and post-socialism - Petrungaro, Stefano (Array, 2019)
The article examines the development of the work discipline and the ethics of work in the shipyard Uljanik in Pula considering the period from the 1980s up to now. Combining oral sources, archival documents, and factory’s magazines, one first conclusion is that in the framework of the self-management system labour discipline was certainly not severe, but neither absent. It was rather in the first half of the 1990s that work discipline vanished, before to be reinstated, in quite new forms, from the second half of the 1990s onwards. Secondly, the article shows how the workers-managers relations worsened in the post-socialist years. This caused a profound emotional detachment by the workers from their work and the factory. In the absence of the older ethics of work, and of a mutual respect between workers and managers (both directors and foremen), what seems to have remained for managing work and the workers is only contemporary labour discipline.